Stabilization of dynamic characteristics of regulation circuit of diesel generator rotation frequency at condition of the parallel operation of the generators - Dvorak, V. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problem of stabilization of dynamic characteristics of the system of automatic regulation of diesel generator rotation frequency at parallel operation with other generators using sliding mode regulator and fuzzy-regulator. Regulation circuit intended for distribution of active power between parallely operating for load generators was designed.